Debate as a method for mastery speaking ability in EFL: How effective is it? - Haliimatussa' Diyyah (Concept : Community Concern for English Pedagogy and Teaching, 2022)
This study aims to find out the effectiveness of debate as a method used in improving students' speaking skills ability in EFL. This was a quantitative study with a pre-experimental research design that used pre-test and post-test as data collection instruments. This research was conducted at Senior High School 1 Babelan Bekasi to 30 students in 11th grade who were the participants of the school English Club. These students were selected by the purposive sampling technique. The data was analyzed statistically by using t-test. The results of this study revealed that: the students’ mean score on the pre-test was 61.03 while their post-test one was 75.90. Additionally, statistical calculation of t-test resulted t-cal (6.30) > t-table (2.045) with significance level of 0.05. Thus, these findings confirmed that the alternative hypothesis (H1) was accepted and the null hypothesis (H0) was rejected. Therefore, this research work concluded that debate used as a method of improving students’ speaking ability is effective. Keywords: Debate method, Speaking ability, EFL students